Eksistensi Pengobatan Alternatif Sanro di Desa Kalotok Luwu Utara - Muhammad Ashabul Kahfi; Syahruddin Syahruddin; Vilsa Vilsa; Muliady Ramli (Prodi Sosiologi FISIP Universitas Teuku Umar, 2022)
Traditional medicine is one form of treatment that is still trusted by the community until now, including in Kalotok Village. Most people choose to entrust their healing through traditional medicine performed by sanro. This study aims to determine the method of treatment carried out by Sanro and the reasons people choose to go to Sanro for treatment. This type of research is a qualitative research with an ethnographic approach. Data were collected through observation, interview, and documentation techniques. The research informants were seven people consisting of two sanro and five patients. The results showed, first, sanro has a treatment method that tends to use simple ingredients that are easily obtained such as plants and water. In addition, sanro also uses a spell that only he knows to blow on the patient. Second, the reason people choose to go to Sanro for treatment is due to several factors, namely economic factors where the cost of Sanro treatment is cheaper; the convenience factor where treatment at Sanro does not require documents such as ID cards, Family Cards, and BPJS; and factors of parental and ancestral habits where patients from childhood were invited to go to Sanro for treatment by their parents and ancestors.